2014
DOI: 10.1002/prot.24688
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-associated aggregate formation of superoxide dismutase-1 is initiated by membrane-targeting loops

Abstract: Copper-Zinc superoxide dismutase 1 (SOD1) is a homodimeric enzyme that protects cells from oxidative damage. Hereditary and sporadic amyotrophic lateral sclerosis may be linked to SOD1 when the enzyme is destabilized through mutation or environmental stress. The cytotoxicity of demetallated or apo-SOD1 aggregates may be due to their ability to cause defects within cell membranes by co-aggregating with phospholipids. SOD1 monomers may associate with the inner cell membrane to receive copper ions from membrane-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Thus, hCCS membrane association is mediated by the combination of globular domains I and II together with the increased interaction surface area provided by domain III–mediated dimerisation. While metal-free, disulphide-reduced wild-type hSOD1 associates with and even penetrates lipid membrane [37,38], on zinc binding, this association is greatly reduced (Fig 5C). Thus, the substrate for hCCS provides little additional membrane attraction, and half of the interfacial interacting surface provided by hCCS homodimerisation is lost on heterodimerisation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, hCCS membrane association is mediated by the combination of globular domains I and II together with the increased interaction surface area provided by domain III–mediated dimerisation. While metal-free, disulphide-reduced wild-type hSOD1 associates with and even penetrates lipid membrane [37,38], on zinc binding, this association is greatly reduced (Fig 5C). Thus, the substrate for hCCS provides little additional membrane attraction, and half of the interfacial interacting surface provided by hCCS homodimerisation is lost on heterodimerisation.…”
Section: Resultsmentioning
confidence: 99%
“…501 AA simulations of cytotoxic demetallated copper-zinc superoxide dismutase 1 found that the protein was both able to adsorb onto PC bilayers, using its metal binding loops, and to complex with clumps of octanol in solution. 502 Another example is PTEN, which hydrolyzes PIP 3 to PIP 2 and contains both a tyrosine phosphatase domain and a membrane binding C2 domain. PTEN interaction with the membrane has been studied using both CG and AA simulations.…”
Section: Membrane-bound Enzymesmentioning
confidence: 99%
“…SOD1, particularly the metal-free state, incorporates within biological membranes and disorders lipid packing (Petkau and Chelack, 1976; Petkau and Copps, 1979; Lepock et al ., 1981). Chng and Strange (2014) used molecular dynamics simulations to show how residues in the conformationally dynamic electrostatic and zinc-binding loops bind octanol and mediate interactions with bilayer surfaces. A C-terminal SOD1 truncation at Leu126 facilitates the adoption of a membrane-penetrant helical structure with several transmembrane helices (Lim et al ., 2015), and similarly, Ala4Val SOD1 self-association created a tetramer capable of functioning as an integral membrane ion channel (Allen et al ., 2012 a ).…”
Section: Sod1 Aggregation In Alsmentioning
confidence: 99%